AGROINDUSTRY BASED AGROPOLITAN INSTITUTIONAL DESIGN WITH ANALYTICAL NETWORK PROCESS - Zulfa Fitri Ikatrinasari Syamsul Maarif Endang Gumbira Sa’id,Tajuddin Bantacut Aris Munandar (Jurnal Teknologi Industri Pertanian, 2009)
Agroindustry based agropolitan institution is required to ensure the sufficiency of supply of raw material and delivery of agroindustry products both quality and quantity. The agropolitan institutions could be adopted from one of of those have been existing. Through the institutional development, local resources value can be optimized according to their potential advantages. The purpose of this research was to establish institutional analysis model in agroindustry based agropolitan. Analytical Network Process (ANP) was used for designing and analyzing the appropriateness of agropolitan institution model. The model was verified and applied at Kabupaten Probolinggo. It was concluded that vertical integrated institution is the most appropriate model for agroindustry based agropolitan. Keywords: agropolitan, agroindustry, analytical network process, institutional design.